2010
DOI: 10.1177/0022034510379602
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacteria in the Caries Process

Abstract: Dental biofilms produce acids from carbohydrates that result in caries. According to the extended caries ecological hypothesis, the caries process consists of 3 reversible stages. The microflora on clinically sound enamel surfaces contains mainly non-mutans streptococci and Actinomyces, in which acidification is mild and infrequent. This is compatible with equilibrium of the demineralization/remineralization balance or shifts the mineral balance toward net mineral gain (dynamic stability stage). When sugar is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
815
1
25

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 969 publications
(875 citation statements)
references
References 95 publications
34
815
1
25
Order By: Relevance
“…Detection of genes to these species fit with the expanded ecological plaque hypotheses that proposes blooming of Actinomyces and non-mutans streptococci in early stages of dental caries [17]. Under this hypothesis, these species set up the environment for more acid-tolerant and acidogenic species that would include S. mutans, S. wiggsiae [33], Actinomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of genes to these species fit with the expanded ecological plaque hypotheses that proposes blooming of Actinomyces and non-mutans streptococci in early stages of dental caries [17]. Under this hypothesis, these species set up the environment for more acid-tolerant and acidogenic species that would include S. mutans, S. wiggsiae [33], Actinomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Samples representing health and caries at the tooth surface and deep in dentin were examined to represent different disease stages. In caries, one might expect increased gene expression related to acid production [17], whereas in health-associated microbiomes gene expression would reflect that of a stable community able to counter acidic attack [6]. Long-term we sought which metatranscriptome activities characterized different clinical states and so that future studies could use the information in risk assessment and as targets for improved anti-caries therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The excreted organic acids result in a strong localized pH drop that can cause lesions of the dental enamel and thus initiate caries development. S. mutans is a common inhabitant of the oral cavity and has long been recognized as one of the causes of dental caries, a highly prevalent biofilm-dependent polymicrobial oral infectious disease (Kutsch and Young, 2011;Takahashi and Nyvad, 2011;Burne et al, 2012). Biofilm formation in S. mutans is readily induced by dietary sugars that are transformed to extracellular polysaccharides by dedicated enzymes, which are therefore important targets of anti-caries strategies (Bowen and Koo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar study have shown that microflora of clinically sound enamel surfaces contains mainly non-mutans Streptococci and Actinomyces, in which acidification is mild and infrequent. [25] Propionibacterium is an acidogenic bacteria with a prevalence of 7.3% of total population from phylum Actinobacteria. Total pooled count in the superficial layer was 12660, and deep layer was found to be 3949.…”
Section: Discussionmentioning
confidence: 99%